(untitled) (Research, Society and Development, 2021)
Since the first civilizations, man has always sought to settle close to the banks of rivers, lakes, and seas, seeking to supply everything from basic to more complex needs. This relationship between man and nature is a subject that is currently being discussed since the use of water resources has generated serious impacts on ecosystems, pollution, contamination and may culminate in the scarcity of this natural good. This study aimed to evaluate the quality of recreational water in spas bathed by the Mosquito stream in the city of Açailândia-MA, according to the standards established by Ordinance No. 888 of 2021 of the Ministry of Health (MS) to CONAMA resolutions No. 274/2000 and No. 357/2005. The initial survey of the study area was carried out using georeferencing by the exploratory tool Google Earth. The criterion for choosing the sampling points was because they are the most frequented recreational bathing activities in the city. Physical-chemical and microbiological tests were performed using the APHA, EPA, SM, and FUNASA techniques. According to the results obtained, most of the parameters analyzed at all points (P1, P2, P3, and P4), such as pH, iron, phosphorus, nitrite, and nitrate indices are not in accordance with Ordinance No. 888 /2021 of MS in addition to high concentrations of thermotolerant bacteria with concentration ≥1600 NMP/100 mL showed that the water body is possibly polluted. Thus, the water at all analyzed collection points is not suitable for primary contact, having a predominance of class 3.